Extending the Harm to Others Paradigm: Comparing Marijuana- and Alcohol-attributed Harms in Washington State - Kerr, William C. (J Psychoactive Drugs, 2020)
Harms attributed to others’ alcohol use have been extensively studied in the US and internationally, but no studies have measured harms from others’ marijuana use. We utilize data from five cross-sectional waves of a survey series with representative samples of Washington state residents conducted every 6 months from 2014 to 2016, after the legalization of adult use marijuana. Harms attributed to others’ drinking and to others’ marijuana use included family and financial problems, assault, harassment and vandalism experiences and accidents due to impaired drivers. Past year harms attributed to others’ marijuana use were reported by 8.4% of the sample, while 21.3% reported alcohol-attributed harms and 4.3% experienced both. Women were more likely to experience harms from either substance. While heavy drinkers were most likely to experience alcohol harms from others’ use, frequent marijuana users reported the least harms from others. About three times as many individuals reported harassment, vandalism or family problems attributed to someone’s alcohol use compared those harms attributed to someone’s marijuana use, with a smaller ratio seen for financial trouble and a wider ratio for physical harm. Harms attributed to other’s marijuana use in Washington were found to be substantial, but lower than harms from others’ drinking.